STATUS GIZI PADA PENDERITA RETARDASI MENTAL (Studi di SLB Dharma Wanita Sidoarjo) - Ari Tri Wanodyo Handayani (Fakultas Kedokteran Gigi Universitas Jember, 2010)
Mental retardation or commonly known as Mental Retardation (RM) is characterized by general intelligence functions that are below average and is accompanied by reduced ability to adapt or behave in adaptive. As a result of the disorder can affect the growth and development. The purpose of this study was todetermine the nutritional status of patients with RM. This study is an observational analytic study with a cross-sectional data retrieval. The study population is students SLB Dharma Wanita Sidoarjo regency. Large study sample was 37 students were randomly taken proportionately based on the severity of the RM. The data retrieved are age, TB and BB. Further data are calculated using the nutritional status of index TB / U and BB / U based on the size of the Z-score WHO NCHS. Analysis of the data using Kruskal Wallis test followed by Mann-Whitney test. Statistical test results showed that there are significant differences in the examination of TB / U in 3 groups of RM. But on examination BB / U data analysis showed no significant difference. Furthermore, the data TB / U were analyzed again using the Mann-Whitney test and found that there are significant differences between mild to RM medium and heavy. There is no official standard measure of nutritional status of patients with RM, so that the measurement is compared to the size of the WHO standard. In anthropometry, most RM patients included in the normal range and tend to be obese. RM moderate and severe sufferers tend to be different, because the more complex as well etiology factors consequences thereof. There is a possibility RM or RM is experiencing severe disruption due to thelinear growth factor complex